Socio-economic and structural barriers in Newcastle disease vaccines uptake by smallholder women farmers in Southeastern Kenya. - Kennedy M Waweru; Dalmas O Omia; Lucy Kiganane; Obadia Miroro; Judith Chemuliti; Isaac K Nyamongo; Salome A Bukachi (PLoS ONE, 2023)
The exploitation of the full benefits of chicken rearing by smallholder farmers in Sub-Saharan (SSA) Africa is often impeded by poultry diseases which is compounded by limited uptake of vaccination. We interrogate the structural and socioeconomic factors associated with vaccine uptake by women farmers in Southeastern Kenya. A mixed methods design with a convergent approach for comparison of quantitative and qualitative findings was adopted. This involved the administration of a cross section survey to 1274 households, conduct of 23 Focus Groups Discussions (FGDs) and 7 Key informant Interviews (KIIs). Chi Square and t-tests were used to identify factors associated with vaccine uptake. Logistics regression analysis was used to identify the influence of the structural and socioeconomic barriers to vaccine uptake. Findings indicate that having knowledge of Newcastle disease (ND) vaccine increases the likelihood of farmers vaccinating their chicken by up to 32.5 times (95% CI [8.46-124.53]) with a 1 unit increase in vaccine knowledge. A farmer's distance away from the nearest ND vaccine vendor was found to reduce the likelihood of farmers vaccinating their chicken by up to 4% (95% CI ([0.93-1.00]) for every 1-kilometre increase in distance away from the vaccine vendors. Farmers who considered vaccines to be effective in preventing ND were 39 times (95% CI [6.23-239.8]) more likely to use ND vaccines than those that did not consider ND vaccine to effective. We surmise that a comprehensive approach that addresses increased ND vaccine knowledge among smallholder women chicken farmers, proximity of ND vendors, as well as cost holds the potential for regular and increased ND vaccine uptake.